(untitled) (Notes in Current Biology, 2015)
Objective of work – forming of method of estimation of circulatory system functional states to reveal groups of students with reduced adaptational potential. Materials: 1107 students took part in disquisition. There were 485 girls and 622 boys at the age from 17 to 20 years. Estimation of individual health of students according to the methods of R. M. Baevski and G. L. Apanasenko has been carried out. Methods are based on Martine’s test with modifications for assessment of individual peculiarities of circulation, permitting to discover disposition of adaptation breakings. Eight functional patterns of circulatory system reaction on physical loading were uncovered. Developing method allows reveal people with heightened risk of sudden breakings of homodynamic, accomplished control of functional coaching of students.